(untitled) (Fourth World Journal, 2026)
In In this article Hailey Allen (Yakama) explores the role of traditional medicine among Yakama women as a vital expression of Indigenous knowledge and a fundamental aspect of Longhouse (Washat) cultural continuity. Referred to as the Seven Drums Religion, or Waashat and Washani, the Longhouse Religion of the Columbia Plateau, including the Yakama, is better understood as a spiritual way of life rather than a formal religion. This study employs an immersive, participatory framework, utilizing elder interviews, Longhouse ceremonies, ceremonial runs, and community knowledge, alongside the harvesting of sacred First Foods: salmon, roots, berries, deer, and water. These elements are central to Longhouse practice. Anchored in the metaphor of Huli, the Sahaptin term for wind, Allen illustrates how Yakama women embody the cyclical and relational transmission of knowledge, thereby fostering cultural continuity and ecological stewardship through generations.